A Survey and Study of the Current Situation of Music Education in High Schools in Northeast China: A Case Study of the High School Attached to Northeast Normal University (Journal of Interdisciplinary Insights, 2024)
This study investigates the current state of music education at the High School Attached to Northeast Normal University in Northeast China. Using a qualitative approach, data were collected through interviews with five music teachers and thirty students. The findings reveal a diverse range of pedagogical practices, blending traditional methods with modern approaches, and highlight significant challenges such as resource limitations and the need for professional development. Both teachers and students acknowledged the cognitive, emotional, and social benefits of music education. However, discrepancies were noted in their perceptions of the primary challenges and priorities. The study underscores the importance of balanced pedagogical strategies, adequate resource allocation, and continuous support for educators. It contributes to the field by providing insights into the specific context of music education in Northeast China and reinforcing the integral role of music education in holistic student development.
Keywords: Music Education; Pedagogical Practices; Qualitative Study; High School; Northeast China; Student Engagement